(untitled) (TAMADDUN NURI JURNALI, 2025)
This article, dedicated to the historical analysis of Samarkand’s national clothing, conducts a thorough study based on source criticism methodology, examining historical sources, miniatures, literary works, and archaeological findings. The periods under study - the 16th and 17th centuries - analyze Samarkand’s clothing not only from a socio-cultural perspective but also from an aesthetic and artistic viewpoint. Miniature art is highlighted as the primary source for depicting clothing from this period, with discussions on the reliability and conventions of these depictions.